2021
DOI: 10.46606/eajess2021v02i01.0060
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the 5E Instructional Model on Physics Academic Achievement Based on Gender and Students’ Ability: A Case of Berekum Senior High Schools in Ghana

Abstract: This study examined the effect of the 5E instructional model on Physics students’ academic achievement based on gender and students’ ability. The study employed a quasi-experimental design using the pre-test, post-test and delayed-post administered instruments to the experimental and control groups. The study involved two instructional strategies (5E instructional model and traditional teaching). Instruments known as Physics Students’ Academic Achievement Test (PSAAT) and Delayed Post Test (DPT) were used to g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
1
1
0
Order By: Relevance
“…The 5Es educational model allows students to be more autonomous in their learning, increases their engagement and interest in science, and improves their learning outcome (Ihejiamaizus et al, 2018) and 5E's constructivist strategy is more effective than the traditional method when used in a classroom setting. This is in line with the study conducted in Ghana that indicated the significant difference between physics high-ability students in the 5E's educational group than those in the traditional group (Appiah-Twumasi et al, 2021).…”
Section: The 5e's Learning Model and Students' Academic Achievementsupporting
confidence: 91%
“…The 5Es educational model allows students to be more autonomous in their learning, increases their engagement and interest in science, and improves their learning outcome (Ihejiamaizus et al, 2018) and 5E's constructivist strategy is more effective than the traditional method when used in a classroom setting. This is in line with the study conducted in Ghana that indicated the significant difference between physics high-ability students in the 5E's educational group than those in the traditional group (Appiah-Twumasi et al, 2021).…”
Section: The 5e's Learning Model and Students' Academic Achievementsupporting
confidence: 91%
“…At this stage, the teachers were working together with the students as facilitators. It was found that Physics learners need the opportunity to think critically, collaborate with other students, participate in problem-solving activities and relate classroom knowledge with practical experiences outside the school setting (Appiah-Twumasi et al, 2021). For instance, in the case of the electromagnetic spectrum, the teacher created a scenario on the formation of the rainbow and asked them to discuss it in their respective groups and present their findings.…”
Section: Data Analysis and Resultsmentioning
confidence: 99%